Tour Guide Competencies and Training Needs: Focus on the tour guides of Arctic Adventures - Sonninen, Paavo Olavi, 1982- (2013)
Companies face many changes and demands from inner and outer business environments. Some of the changes create training and development needs. Training and development actions are aimed to enhance individual competencies, which can be defined as skills, knowledge, behaviour, attitudes and values. The actions must be aligned with the company strategy to ensure transfer of training. This can be done by following a four step human resource development cycle. First, a training needs analysis is conducted to determine the actual and expected levels of competencies. The second phase will concentrate on designing the correct training actions, since wrongly designed and delivered actions are costly. The third step will deliver the right training actions. Finally the last phase will evaluate the actions, to see whether the set objectives were reached. The purpose of this research was to determine whether any training needs exist among the tour guides of Arctic Adventures and, in addition, whether future legislation poses threats. This was done by conducting a training needs analysis. The training needs analysis determined the necessary competencies and their current levels. The actual levels were compared to the expected levels, to determine any possible training and non-training needs. The team of guides was chosen due to the multiple competency demands set by the nature of work. In everyday work, guides must work with quality and safety related factors. In addition, the current and future legislation and industry standardization caused this topic to be of great interest. The findings revealed a vast amount of required competencies in the occupation of an outdoor activity guide. Many of them were industry specific, and could be transferred between companies and countries. The training needs analysis also revealed few training needs. The current and expected competency levels were high and discrepancies were small. In addition the research discovered a demand for more formal education in Icelandic tourism, better ...